Effect of phacoemulsification, intraocular lens implantation, and trabeculectomy on angle-closure glaucoma merged with cataract - Qun Wu (Journal of Hainan Medical University, 2016)
Objective: To explore the clinical effect of phacoemulsification, intraocular lens implantation, and trabeculectomy in the treatment of angle-closure glaucoma merged with cataract. Methods: A total of 80 patients with angle-closure glaucoma merged with cataract who were admitted in our hospital from May, 2015 to May, 2016 were included in the study and randomized into the observation group and the control group. The patients in the control group were given phacoemulsification and intraocular lens implantation. On this basis, the patients in the observation group were given trabeculectomy. The vision, intraocular pressure, central anterior chamber depth, and visual field before operation, 1 week, 1 month, and 3 months after operation in the two groups were detected. Results: In the control group, 1 month after operation, while in the observation group, 1 week after operation, the vision was significantly improved, the intraocular pressure was significantly reduced, the central anterior chamber depth was significantly increased, and the average visual field defect value and average standard deviation value were significantly improved when compared with before operation (P<0.05); moreover, the improved degree in the observation group was significantly superior to that in the control group (P<0.05). Conclusions: Phacoemulsification, intraocular lens implantation, and trabeculectomy in the treatment of angle-closure glaucoma merged with cataract can effectively increase the central anterior chamber depth, reduce the intraocular pressure, and improve the vision; therefore, it deserves to be widely recommended in the clinic.